METODE REGRESIF DALAM PEMBELAJARAN SEJARAH: PENDEKATAN TEORETIS DAN IMPLIKASINYA - Krismawarni, Krismawarni; Ediyono, Suryo (Universitas Negeri Malang, 2025)
This article aims to discuss the concept, main objectives, characteristics, and application of the regressive method in history learning, as well as its theoretical and practical implications, which can be an alternative in improving students' understanding of history as an event. This study uses a descriptive qualitative approach, with data obtained through a literature review. Analysis was conducted on literature sources relevant to the discussion, in the form of articles, books, and educational documents. This approach was chosen because it is relevant in exploring contextual understanding of the regressive method in history learning. The regressive method in history learning emphasizes how the historical thinking process can begin from contextual conditions and then trace how historical roots move regressively or backward. This approach is relevant to the discussion that builds conditions between present reality and past dynamics that will encourage students to think critically, reflectively, and contextually. The contribution of the regressive method within the framework of this transformation of history learning can support quality education, namely meaningful, adaptive, relevant, and contextual learning, which can be a valuable investment for students, namely historical reasoning skills and building awareness of social dynamics. This article describes how the implementation strategy in history learning with potential and challenges that can be considered in combining learning models with the selection of methods and their implementation as one of the current history learning strategies. The results of the analysis provide an understanding that the regressive method has a role in improving the quality of history learning in line with 21st-century education, namely, high-level thinking skills and relevance to real life. Furthermore, this regressive method is part of the supporting aspects in achieving global development goals, namely sustainable quality education.